An Erasmus Adventure and It’s Bringings… - Mine Akkurt (Türk Kütüphaneciliği)
The purpose of this paper is to share the period of Erasmus Staff Mobility Training which I attended in 16-22 July 2012 in England, Exeter University, and to share the writing process of a case study that have been published in an international book for library professionals through personal connections that has been gained during the Erasmus Staff Training.